Establishment of a methodology for determination of the strength condition of fixed offshore jacket structures in deepwater, based on probabilistic model and reliability theory, and its application in Vietnamese sea conditions - Quan, Mai Hong; Anh, Bui The (Petrovietnam Journal, 2012)
Exploitation of oil and gas fields in deepwater is an increasing tendency worldwide; this requires the installation of production platforms with high safety in the most unfavorable conditions. This has encouraged new approaches to description of the environmental conditions by statistical modelling, then establishment of appropriate methods for structural analysis and design of deepwater platforms, from fixed jacket to anchored floating platforms. In the framework of this paper, the authors present the methodology for expressing the strength condition by a probabilistic model for estimate of the safety based on reliability theory, in order to analyse fixed platform jacket structure in deepwater aimed to be applicable in Vietnamese sea conditions from 200 - 400m depth. The paper content is developed from authors’ research results in the National research Project KC.09.15/06-10.